2019
DOI: 10.1002/1873-3468.13674
|View full text |Cite
|
Sign up to set email alerts
|

How the protonation state of a phosphorylated amino acid governs molecular recognition: insights from classical molecular dynamics simulations

Abstract: Physicochemical properties of proteins are controlled mainly by post‐translational modifications such as amino acid phosphorylation. Although molecular dynamics simulations have been shown to be a valuable tool for studying the effects of phosphorylation on protein structure and dynamics, most of the previous studies assumed that the phosphate group was in the unprotonated (PO32-) state, even though the protonation state could in fact vary at physiological pH. In this study, we performed molecular dynamics sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Since the pKa of the phosphorylated residues is around six [ 37 ], in reality it can fluctuate between and . Recent studies have suggested the importance of the protonation state of phosphorylated residues for molecular interactions [ 38 ], hence influencing salt bridge formation and the conformational ensemble. Therefore, this is suggested to be included in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pKa of the phosphorylated residues is around six [ 37 ], in reality it can fluctuate between and . Recent studies have suggested the importance of the protonation state of phosphorylated residues for molecular interactions [ 38 ], hence influencing salt bridge formation and the conformational ensemble. Therefore, this is suggested to be included in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…K d , crucial in drug discovery, quantifies the strength of interaction between a ligand and its target. Techniques like SPR and ITC may struggle to measure binding affinities for weak or transient complexes, limiting the assessment of potential drug candidates' efficacy and specificity [12,13]. In summary, traditional methods of acquiring structural and K d data face significant challenges, including financial constraints, time intensiveness, scalability limitations, and difficulties in capturing dynamic interactions.…”
Section: Of 11mentioning
confidence: 99%
“…[265][266][267] The same argument applies to the efficient use of polarizable force fields when dealing with PTM protonation state. 268,269 Aside from parameterization improvements, advances in structure prediction methodology raise the possibility of predicting covalently modified proteoform conformations. Software like DeepMind's AlphaFold, along with the Baker lab's RoseTTaFold, have now revolutionized protein structure prediction with their machine learning-based template-free methods that, in most cases, can rival experimental structure quality.…”
Section: Outlooks On Ptm Modeling and Simulationsmentioning
confidence: 99%
“…265–267 The same argument applies to the efficient use of polarizable force fields when dealing with PTM protonation state. 268,269…”
Section: Outlooks On Ptm Modeling and Simulationsmentioning
confidence: 99%